Critical analysis of risk factors and outcome of placenta previa - Rosenberg, Tom; Pariente, Gali; Sergienko, Ruslan; Wiznitzer, Arnon; Sheiner, Eyal (Archives of gynecology and obstetrics, 2011)
Objective To investigate risk factors and pregnancy outcome of patients with placenta previa. Methods A population-based study comparing all singleton pregnancies of women with and without placenta previa was conducted. Stratified analysis using multiple logistic regression models was performed to control for confounders. Results During the study period, there were 185,476 deliveries, of which, 0.42% were complicated with placenta previa. Using a multivariable analysis with backward elimination, the following risk factors were independently associated with placenta previa: infertility treatments (OR 1.97; 95% CI 1.45–2.66; P < 0.001), prior cesarean delivery (CD; OR 1.76; 95% CI 1.48–2.09; P < 0.001) and advanced maternal age (OR 1.08; 95% CI 1.07–1.09; P < 0.001). Placenta previa was significantly associated with adverse outcomes such as peripartum hysterectomy (5.3 vs. 0.04%; P < 0.001), previous episode of second trimester bleeding (3.9 vs. 0.05%; P < 0.001), blood transfusion (21.9 vs. 1.2%; P < 0.001), maternal sepsis (0.4 vs. 0.02%; P < 0.001), vasa previa (0.5 vs. 0.1%; P < 0.001), malpresentation (19.8 vs. 5.4%; P < 0.001), postpartum hemorrhage (1.4 vs. 0.5%; P = 0.001) and placenta accreta (3.0 vs. 1.3%; P < 0.001). Placenta previa was significantly associated with adverse perinatal outcomes such as higher rates of perinatal mortality (6.6 vs. 1.3%; P < 0.001), an Apgar score <7 after 1 and 5 min (25.3 vs. 5.9%; P < 0.001, and 7.1 vs. 2.6%, P < 0.001, respectively), congenital malformations (11.5 vs. 5.1%; P < 0.001) and intrauterine growth restriction (3.6 vs. 2.1%; P = 0.003). Using another multivariable logistic regression model, with perinatal mortality as the outcome variable, controlling for confounders, such as preterm birth, maternal age, etc., placenta previa was not found as an independent risk factor for perinatal mortality (weighted OR 1.018; 95% CI 0.74–1.40; P = 0.910). Conclusions Infertility treatments, prior cesarean section, and advanced maternal age are independent risk factors for placenta previa. An increase in the incidence of these risk factors probably contributes to a rise in the number of pregnancies complicated with placenta previa and its association with adverse maternal and perinatal outcomes. Careful surveillance of these risk factors is recommended with timely delivery in order to reduce the associated complications.